Kinerja Keuangan Bank Syariah di Indonesia - Nugroho Heri Pramono; Ardian Widiarto (Accounthink, 2019)
This study aims to determine the effect of profit-sharing based financing, non-performing financing (NPF), Sharia Supervisory Board (DPS), zakat performing ratio (ZPR), inflation, and interest rates (BI rate) both simultaneously and partially on financial performance Islamic banks in Indonesia. The sample used in this study was 40 Islamic banks in Indonesia in 2012 until 2016. The sampling technique used was simple random sampling. The results showed that simultaneous profit-sharing based financing, non-performing financing (NPF), Sharia Supervisory Board (DPS), zakat performing ratio (ZPR), inflation, and interest rates (BI rate) variables had an effect on the financial performance of Islamic banks. Partially, the variables that influence the financial performance of Islamic banks are the variable non-performing financing (NPF) and the zakat performing ratio (ZPR). While variables that do not affect the financial performance of Islamic banks are profit-based financing variables, Sharia Supervisory Board (DPS), inflation, and interest rates (BI rate).